1995
DOI: 10.1084/jem.181.6.2059
|View full text |Cite
|
Sign up to set email alerts
|

CD28 signals through acidic sphingomyelinase.

Abstract: SummaryT cell receptor recognition of antigen can lead either to T lymphocyte differentiation and proliferation or to a state of unresponsiveness, which is dependent on whether appropriate costimulatory signals are provided to the mature T cell. We have investigated a novel intracellular signaling pathway provided by the costimulatory molecule CD28. CD28 engagement triggers the activation of an acidic sphingomyelinase (A-SMase), which results in the generation of ceramide, an important lipid messenger intc~i~e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 53 publications
3
98
1
Order By: Relevance
“…This was particularly evident after ligation of CD28 (Fig. 9B), which promotes ASM activation and ceramide release in the outer leaflet of the plasma membrane (27). Supporting the hypothesis that the N 3 -C 6 -cer codistributed with endogenous ceramides released upon receptor ligation, pre-exposure of T cells to the ASM inhibitor amitriptyline largely prevented its redistribution into activation clusters after CD28 ligation (Fig.…”
Section: Incorporated N 3 -C 6 -Cer Does Not Affect T Cell Activationsupporting
confidence: 48%
See 1 more Smart Citation
“…This was particularly evident after ligation of CD28 (Fig. 9B), which promotes ASM activation and ceramide release in the outer leaflet of the plasma membrane (27). Supporting the hypothesis that the N 3 -C 6 -cer codistributed with endogenous ceramides released upon receptor ligation, pre-exposure of T cells to the ASM inhibitor amitriptyline largely prevented its redistribution into activation clusters after CD28 ligation (Fig.…”
Section: Incorporated N 3 -C 6 -Cer Does Not Affect T Cell Activationsupporting
confidence: 48%
“…Similarly, physiological acid SMase (ASM) activation after death receptor ligation followed by ceramide release interferes with relay of TCR signaling by abrogating store-operated Ca 2+ entry, NF-AT activation, and IL-2 synthesis (25,26). However, in other situations, activation of SMases appears to modulate T cell activation (27)(28)(29), indicating that both the amount and/or compartmentalization of ceramides at stimulatory interfaces needs to be tightly controlled. In support of this hypothesis, Ab-based detection studies have revealed that ceramides are largely excluded from the center of an established immune synapse (IS) in favor of the lamellum (29).…”
mentioning
confidence: 99%
“…Three forms of SMases are candidates for SM hydrolysis. Acid SMase (pH optimum 4.5 ± 5.0) has been associated in apoptosis signaling triggered by TNFa (Wiegmann et al, 1994), antiFas (Cifone et al, 1994), and anti-CD28 (Boucher et al, 1995); activation of a membrane bound neutral SMase (pH optimum 7.4) has also been described with TNFa (Wiegmann et al, 1994), anti-Fas antibody (Tepper et al, 1995), IL-1b (Mathias et al, 1993) and daunorubicin ; finally, a cytosolic neutral SMase has been implicated in vitamin D3 induced differentiation (Okazaki et al, 1994). A recent study by Kolesnick's group clearly demonstrated that acid SMase-deficient human lymphoblasts as well as lung endothelium, thymus and spleen of acid SMase knockout mice are defective in IRinduced apoptosis (Santana et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…indeed several mediators known to increase the intracellular levels of ceramide are involved in the early immune response, i.e., TCR triggering, IL-1␤, TNF-␣, IFN-␥, and CD28 ligation (10,(12)(13)(14)(15)(32)(33)(34). When the T cell forms Ag-specific conjugates with APC, a supramolecular activation cluster is observed at the T-APC contact zone.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways with the potential to increase PP2A activity exist in T cells during their encounter with APC. For instance, triggering of the TCR (10), CD5 (11), CD28 (12), and cytokine receptors for IL-1␤ (13) and TNF-␣ (14, 15) activates sphingomyelinase. Sphingomyelinase in turn hydrolyzes sphingomyelin to generate the lipid second messenger ceramide that is a potent activator of ceramide-activated protein phosphatase belonging to the PP2A family (16 -18).…”
mentioning
confidence: 99%